Acute Effect of Repeated Sprints on Interlimb Asymmetries During Unilateral Jumping. Issue 8 (August 2021) - Bishop, Chris; McAuley, Will; Read, Paul; Gonzalo-Skok, Oliver; Lake, Jason; Turner, Anthony
Abstract : Abstract: Bishop, C, McAuley, W, Read, P, Gonzalo-Skok, O, Lake, J, and Turner, A. Acute effect of repeated sprints on interlimb asymmetries during unilateral jumping. J Strength Cond Res 35(8): 2127–2132, 2021—The aim of this study was to investigate the effects of multiple repeated sprints on unilateral jump performance and interlimb asymmetries. Eighteen recreationally active men performed 3 single-leg countermovement jumps (SLCMJ) as baseline data. The repeated sprint protocol was 6 × 40 m with 20 seconds of passive rest between each sprint. This protocol was conducted 4 times, each set separated by 4 minutes of rest. Within that rest period, subjects performed one SLCMJ on each limb after 2 minutes of rest. A 1-way analysis of variance showed significant reductions ( p < 0.05; effect size [ES] = −0.52 to −0.99) in jump height on both limbs after each set relative to baseline. Interlimb asymmetries increased at each time point and ranged from 7.62 to 14.67%, with significant increases in asymmetry seen after sets 3 ( p = 0.046) and 4 ( p = 0.002). Significant increases in sprint time were shown between sprints 1 and 6 in each set ( p ⩽ 0.01). A fatigue index (%) was also calculated and showed an exponential increase from 5.74% (set 1) to 13.50% (set 4), with significant differences between all sets ( p < 0.001) with the exception of sets 3 and 4. Results from this study show that a 6 × 40-m repeated sprint protocol is a sufficient dose for implementing acute fatigue in recreationally active subjects. This was manifested by reductions in jump height at all time points and jump height asymmetries after the third and fourth sets. These findings indicate that jump height from unilateral jump testing may be a useful metric to use during the monitoring process in recreationally trained athletes.